Pemilihan Deteksi Tepi Terbaik Untuk Menganalisa Citra Ultrasonografi Kehamilan - Rizki, Syafrika Deni; Sumijan, S; Putra, Okta Andrica (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
In its development, image processing is very helpful for solving problems faced by humans. Imaging processing is an image processing technique of an object to distinguish the background and the object to be analyzed. This research uses a segmentation method that can distinguish between objects and backgrounds. Analyzing objects from ultrasound images requires the expertise of an experienced doctor. In addition, there are artificial factors that make automated analysis complicated. We aim to improve natural imagery. Therefore to overcome the potential difficulties in analysis, we present four Comparison of Edge Detection, namely Gradient Image, Roberts Operator, Sobel Operator and Prewitt Operator. In image processing, data accuracy and accuracy are required as well as knowledge of statistics because image processing is related to data processing. The result of this research is to determine which edge detection is more appropriate for analyzing ultrasound images. The conclusion from this research is that from the four operators that were tried, the results of the testing process showed that the Prewit operator succeeded in detecting existing objects, even objects that function as background were successfully detected. The resulting edge detection is smoother compared to other operators.